Enhancing Elementary Students’ Mathematical Problem-Solving Skills Through Mindfulness-Based Emotional Coaching and Living Values Education (LVE) - Assyifa Indar Apriana; Meli Baedahsari; Mutiara Kharisma; Dina Pratiwi Dwi Santi; Siska Firmasari (STAI Hubbulwathan Duri, 2025)
Mathematical problem-solving skills among elementary school students in Indonesia remain below expected standards according to international and national assessments. Limited emotional regulation and insufficient internalization of positive values are identified as contributing factors. Integrating social-emotional approaches into mathematics learning is therefore essential. This study examined the effectiveness of an emotional coaching program integrating mindfulness practices and Living Values Education (LVE) in enhancing students’ mathematical problem-solving abilities. A mixed-methods approach with a sequential explanatory design was employed. The quantitative phase involved a pretest–posttest design with 25 fourth-grade students selected through purposive sampling at an elementary school in Cirebon, Indonesia. Students’ mathematical problem-solving skills were measured using a structured test and analyzed using a paired sample t-test. The qualitative phase consisted of semi-structured interviews analyzed thematically to explore students’ emotional regulation, learning focus, and problem-solving strategies. The results showed a statistically significant improvement in students’ mathematical problem-solving performance following the intervention. Qualitative findings indicated enhanced emotional regulation, increased concentration, and the use of more reflective problem-solving strategies. Mindfulness practices contributed to students’ self-awareness and emotional calmness, while Living Values Education fostered responsibility, patience, and cooperation in learning. The findings indicate that emotional coaching grounded in mindfulness and Living Values Education effectively supports both cognitive and emotional development, offering a holistic approach to improving elementary students’ mathematical problem-solving skills.